Vaccination, Compliance with Preventive Measures and Mental Health during COVID-19 among Adults in Bangladesh: Do Vaccination and Compliance with Preventive Measures Improve Mental Health? - Singha, Bipasha; Karmaker, Shamal Chandra; Islam, M. Mazharul; Eljamal, Kareman; Saha, Bidyut Baran (International Journal of Statistics in Medical Research, 2022)
Background and Objective: In addition to the reduction of risk of COVID-19 transmission and mortality, vaccination and compliance with the preventive measures of COVID-19 may have important additional benefits for the improvement of mental health. This study examined the levels and determinants of vaccination, compliance with preventive measures, and anxiety, depression and stress among Bangladeshi adults. It also examined the effects of vaccination and compliance with preventive measures on mental health status among Bangladeshi adults. Methods: Data for the study come from an online survey conducted during November and December 2021 among Bangladeshi adults. A total of 615 adults participated in the survey. A 21-item Depression, Anxiety, and Stress scale (DASS 21) were used for collecting data on mental health. Both descriptive and inferential statistical methods including multiple logistic regression were used for data analysis. Results: About 69% of Bangladeshi adults were vaccinated with at least one dose; 87% of adults believed that vaccines are moderate to highly effective in reducing COVID-19 infection. Among the preventive measures during a pandemic, the level of complete compliance with wearing masks and hand washing was almost universal, while the compliance level with other preventive measures was moderate. Vaccinated people had a 55% (OR=0.45; 95%CI:0.26-0.82), 67% (OR=0.33; 95%CI:0.12-0.91), and 44% (OR=0.56; 95%CI:0.27-0.97) lower chance of suffering from depression, anxiety, and stress, respectively than non-vaccinated people. People with complete compliance had 64% (OR= 0.36; 95%CI:0.18-0.72), 71% (OR=0.29; 95%CI:0.15-0.58), and 74% (OR=0.26; 95%CI:0.13-0.50) lower risk of suffering from depression, anxiety, and stress, respectively, than respondents with irregular preventive behaviors. Conclusion: This study documents the important psychological benefits of vaccination and compliance with preventive measures of COVID-19.